Cost and Health Care Utilization Implications of Bariatric Surgery Versus Intensive Lifestyle and Medical Intervention for Type 2 Diabetes. Issue 9 (19th July 2017) - Banerjee, Souvik; Garrison, Louis P.; Flum, David R.; Arterburn, David E.
Abstract : Objective: The aim of this study was to compare the cost and health care utilization of patients with obesity and type 2 diabetes mellitus (T2DM) randomized into either Roux‐en‐Y gastric bypass (RYGB) surgery or an intensive lifestyle and medical intervention (ILMI). Methods: This analysis ( N  = 745) is based on 2‐year follow‐up of a small randomized controlled trial (RCT); adult patients with obesity and T2DM were recruited between 2011 and 2012 from Kaiser Permanente Washington. Comparisons were made for patients randomized into either RYGB ( N  = 15) or ILMI ( N  = 17). Results: There were no significant cost savings for RYGB versus ILMI patients through the follow‐up years. Pharmacy cost was lower for RYGB versus ILMI patients by about $900 in year 2 versus year 0; however, inpatient and emergency room costs were higher for surgery patients in follow‐up years relative to year 0. Median total cost for nonrandomized patients was higher in year 0 and in year 2 compared to randomized patients. Conclusions: Bariatric surgery is not cost saving in the short term. Moreover, the costs of patients who enter into RCTs of RYGB may differ from the costs of those who do not enter RCTs, suggesting use of caution when using such data to draw inferences about the general population with obesity.